Spirituality in the workplace in South Africa: A systematic literature review - de Wet, Tessa; Heyns, Marita; Marais-Opperman, Vasti (Koers (Potchefstroom, South Africa), 2024)
Background:Spirituality is a multi-dimensional concept that involves a person’s pursuit of well-being through connections with oneself, others, nature, and the transcendent. Spirituality in the workplace encompasses the integration of spirituality into organisational and work dynamics.Purpose:This systematic literature review sourced and synthesised empirical research evidence to explore the influence and experience of perceived spirituality in the workplace on workers in the South African workplace.Methodology:The systematic literature review plan was registered on the Open Science Framework. Keyword searches were conducted, and studies were screened following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) process and checklist. Specific inclusion and exclusion criteria informed the second screening and review of articles. Thirty-one articles fit the specific criteria for inclusion in the review. Relevant data was extracted using thematic analysis.Findings/results:The respondents in the various studies spanned public and private sectors, encompassing various professions and ethnicities. The articles reviewed indicated that the perception of spirituality in the workplace manifested in a variety of constructs and concepts, positively influencing and impacting individual, group, and organisational levels. The review indicated that nuanced contextual differences may play a role in the experience of spirituality in the South African workplace.Practical implications:The literature review suggests potential constructs for understanding workplace spirituality in South Africa, with future research potential for constructing a framework fostering a pluralistic model of spirituality at work.Originality/value:Understanding spirituality in the South African work context could assist in bringing about more productive and healthy organisations. Provided data also forms a basis for developing a potential framework for implementing spirituality in South African organisations.